The effect of using wordwall as a primaryv digital tool to increase seventh-grade EFL learners vocabulary knowledge - Veintimilla Duque, Oyuki Betzabe (2025)
In today's educational context, where technology and innovation serve as fundamental elements in educational practices and considering that digital tools have become more popular, teachers must learn to use them and offer new ways of learning. For instance, one resource that has emerged to facilitate learning is Wordwall, which contains a wide range of templates through which teachers can promote vocabulary activities that facilitate the acquisition of new words and concepts specific to the target language. The current research was made to analyze the impact of employing Wordwall as a primary digital tool to foster seventh-grade EFL learners’ vocabulary through a quantitative method using print questionnaires such as pre-test, post-test, and Likert surveys as instruments. The study was conducted in a public institution with students from low-income families who have always received a traditional education. The results showed an improvement in vocabulary acquisition after receiving instruction using Wordwall. It was also found that students´ oral communication skills improved after an intervention, thus demonstrating that the use of Wordwall aligns with new current pedagogies that promote active learning and the personalization of educational activities.